Pluralisme Agama Bukan Nihilisme: Respon Untuk Kaum Fundamentalis - Moh. Shofan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
This article will see the problem of pluralism through multi- dimensional approach. The plural society is not only the characteristic of modern industrial society, but also the characteristic of Islamic society, since the Prophet (PBUH) era. Normatively, al-Quran clearly rejects the exclusif way of life. In todays life, admitting diversity but having no will to create harmony will cause an unendless problem. Pluralism is the divine design which must be applied in manner and action. This must not stop in the discourse, but more practical. Human being is not merely a homo pluralist, who appreciate the diversity, but homo multiculturalist, who believe that in a plural relation there must be build real actions based on equality and justice.